Towards a methodology of applying the paribhāṣās in the KauśikaSūtra (I) (with special reference to 7.1) - Rotaru, Julieta (Acta Orientalia Vilnensia, 2008)
University of Bucharest The KauśikaSūtra (KauśS) represents a complex work of the Śaunaka school, collected from various sources of Atharvavedic ritual literature. Bloomfield considered that the KauśS was compiled at a certain time from different materials with clearly individual characters and that the redactor(s) did not try or did not succeed in harmonising and unifying the text by removing the discrepancies. One of the effects which would follow from these inconsistent revisions would be that the general rules would be applied strictly to some passages and loosely or not at all to others. A systematic study regarding a methodology for applying metarules to the KauśS is wanting. The present work represents such an attempt, restricted to the elucidation of the paribhāṣā 7.1. Following an exhaustive analysis of all its potential uses, underlined by a new translation of the respective passages, it is noted that the metarule is quite consequently applied. One of the questions arising from this is whether Kauśika had in mind some of these metarules at the time of his composition and the later redactor(s) attempted to maintain a high degree of consistency in applying them to the newly introduced fragments. Secondarily, the paper addresses another issue, the use of the preverb pra in prāśnāti and prāśayati allegedly as a tool for disambiguation in the KauśS.